Podnikatelský záměr - nákup nového stroje - Lokvencová, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Hlavním cílem diplomové práce je podnikatelský záměr – nákup nového stroje. Dílčím cílem je navrhnout různé varianty financování a vybrat nejvhodnější z nich a poté posoudit efektivnost investice. Teoretická část je zaměřena na vymezení základních pojmů týkající se podniku a jeho okolí, podnikatelského plánu, rizik a zhodnocení ekonomické efektivnosti investice. V praktické části se zabývám konkrétním podnikatelským záměrem a to nákupem nového stroje ve firmě. Zvažuji zde různé varianty financování a následně vybírám nejvhodnější z nich a zároveň posuzuji, zda je investice pro podnik přijatelná či nikoliv.

The main objective of this thesis is a business plan - buying a new machine. The operational objective is to design a variety of financing options and choose the best of them, and then assess the efficiency of investment. The theoretical part is focused on the definition of basic concepts relating to the company and its surroundings, business plan, risk assessment and evaluation of economic efficiency of investment. In the practical part deals with specific business purpose and the purchase of a new machine in the company. I'm thinking here of various financing alternatives and then choosing the best of them while judging whether the investment is acceptable for the company or not.
Business plan - purchase of a new machine
Keywords: Investice; zdroje financování; podnikatelský plán; ekonomická efektivnost; Investments; sources of financing; business plan; economic efficiency